EXPLORING THE CREATIVE MATHEMATICAL REASONING OF MATHEMATICS EDUCATION STUDENT THROUGH DISCOVERY LEARNING - Titin Masfingatin; Wasilatul Murtafiah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
Discovery learning is a learning model that enhancescreative thinking skill including develops students' creative mathematical reasoning. Creative mathematical reasoning process includes novelty, plausibility, and mathematical foundation. This research aims to describe students’ creative mathematical reasoning of the mathematics education department on Geometry. The data was collected based on the observation and individual evaluation of students.The results showed that Discovery Learning can (1) grow as much as 35.48% of students have complete creative mathematical reasoning (novelty, plausibility, and mathematical foundation), (2) grow as much as 64.52% of students have incomplete creative mathematical reasoning, and (3) grow novelty by 77.42%.